Development of wood carving furniture technology in Jepara. Issue 1 (July 2020) - Supriyatna Marizar, Eddy; Widya Mutiara, Maitri; Purna Irawan, Agustinus
Abstract: The majority of wood carving technology in Jepara is still conventional. The production process is done traditionally and manually (handmade), especially in wood carving that is applied to furniture. The impact is the production process becomes slow and the quality of the product cannot be achieved optimally. Optimization of production is needed to match the demands of the export market. Therefore, production technology is needed to meet the wants and needs of the export market. In this context, wood carving furniture that is designed for the export market should be realized with mass-processed machine technology solutions. The current development in Jepara that is happening is the production process in a modern way, but the product does not use carvings or decoration. Though wood carving can be made using a CNC router. Thus in the era of globalization, the development and design of wood carving furniture production technology in Jepara should properly use processes based on modern technology, machinery, skills, and mind-set changes as industrial products, including the development of human resources. In this case: training, coaching and mentoring should be done continuously, both by the government, universities and associations. This qualitative research uses a multidisciplinary approach, namely: technology, marketing, and design.